2016
DOI: 10.1111/hae.12954
|View full text |Cite
|
Sign up to set email alerts
|

Experience of a new high‐purity factor X concentrate in subjects with hereditary factor X deficiency undergoing surgery

Abstract: These data demonstrate that pdFX is safe and effective as replacement therapy in five subjects with mild-to-severe FX deficiency undergoing surgery on seven occasions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 15 publications
1
47
0
Order By: Relevance
“…During extended prophylactic use of pdFX in subjects who had previously received treatment with other clotting factors—including 3 subjects who had received pdFX for compassionate use prior to study entry—no evidence was seen in this study population for the development of FX inhibitors. These data are consistent with previous pdFX studies in patients ≥12 years old with moderate to severe FXD, who also showed no sign of inhibitor development . In addition, no cases of FX inhibitor development have been reported in postmarketing safety surveillance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…During extended prophylactic use of pdFX in subjects who had previously received treatment with other clotting factors—including 3 subjects who had received pdFX for compassionate use prior to study entry—no evidence was seen in this study population for the development of FX inhibitors. These data are consistent with previous pdFX studies in patients ≥12 years old with moderate to severe FXD, who also showed no sign of inhibitor development . In addition, no cases of FX inhibitor development have been reported in postmarketing safety surveillance.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have been published on the use of pdFX in subjects ≥12 years old with hereditary FXD . However, data describing the use of FX‐specific treatments in children <12 years old are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of 16 subjects with moderate or severe FX deficiency (plasma FX:C <5 IU dL −1 ) demonstrated the safety and efficacy of pdFX at doses of 25 IU kg −1 administered to treat spontaneous, menorrhagic and traumatic bleeding . Similar results were observed when pdFX was administered to five subjects with mild‐to‐severe FX deficiency (plasma FX:C <20 IU dL −1 ) for haemostatic cover before and after surgery . Independently, breakthrough bleeding in a 9‐year‐old child was shown to be effectively prevented with pdFX maintained at a trough level of 6 IU dL −1 (72 h post dose) over a 3‐year period , supporting the observation that low plasma FX levels are adequate for haemostasis in some subjects.…”
Section: Introductionmentioning
confidence: 72%